Oral isotretinoin and photoaging: A review. (1st June 2020) - Honeybrook, Adam; Bernstein, Eric
Abstract: Introduction: Over the past 20 years, evidence has emerged indicating oral isotretinoin could be considered a potential treatment for photoaged skin. In this review, we provide a succinct overview of the available evidence and provide commentary on the current and future directions for utilizing oral isotretinoin as a potential treatment for photoaging. Methods: We prepared a review protocol and searched the PubMed and Cochrane databases for relevant literature published between January 1982 and April 2020. Using a defined keyword search, a total of 23 papers were initially identified by the main author. Two authors independently reviewed each of the 23 articles, and 6 articles were deemed relevant to this study. Results: Of the six studies included in this review, three were randomized clinical trials, one was a nonrandomized clinical trial and two were prospective cohort studies. All studies were conducted between 2000 and 2015. Across all 6 studies, 251 patients were recruited, with a mean of 42 patients per study. Four studies were in favor of isotretinoin to improve photoaged skin, 1 study showed no benefit, and 1 study showed no benefit when compared to topical tretinoin treatment. Of the studies available, many were hampered by methodological challenges. Conclusion: Oral isotretinoin may be useful for treating photoaging but there is currently insufficient evidence to support its use. In comparison with other established anti‐photoaging treatments, it is not clear whether the potential benefits of oral isotretinoin outweigh the potential risks.